2010
DOI: 10.1182/blood-2009-08-237370
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Vpr up-regulates expression of ligands for the activating NKG2D receptor and promotes NK cell–mediated killing

Abstract: HIV up-regulates cell-surface expression of specific ligands for the activating NKG2D receptor, including ULBP-1, -2, and -3, but not MICA or MICB, in infected cells both in vitro and in vivo. However, the viral factor(s) involved in NKG2D ligand expression still remains undefined. HIV-1 Vpr activates the DNA damage/stress-sensing ATR kinase and promotes G(2) cell-cycle arrest, conditions known to up-regulate NKG2D ligands. We report here that HIV-1 selectively induces cell-surface expression of ULBP-2 in prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
156
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(165 citation statements)
references
References 50 publications
9
156
0
Order By: Relevance
“…To gain insights into the molecular mechanisms regulating the expression of activating ligands in infected cells, we investigated the role of DDR, a host cell pathway that positively affects the expression of activating ligands (35)(36)(37)(38)(39)(40)(41)(42)(43) and that it is activated by HCMV (26,27,(29)(30)(31)(32)(33)(34). Nevertheless, in HCMV-infected HFFs, MICA, ULBP3, and PVR were still increased even when ATM, ATR, and/or DNA-PK were knocked down, thus indicating that these DDR kinases are not involved in the HCMV-mediated ligand stimulation, similar to what has been reported for murine NKG2DL during murine CMV infection (78).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To gain insights into the molecular mechanisms regulating the expression of activating ligands in infected cells, we investigated the role of DDR, a host cell pathway that positively affects the expression of activating ligands (35)(36)(37)(38)(39)(40)(41)(42)(43) and that it is activated by HCMV (26,27,(29)(30)(31)(32)(33)(34). Nevertheless, in HCMV-infected HFFs, MICA, ULBP3, and PVR were still increased even when ATM, ATR, and/or DNA-PK were knocked down, thus indicating that these DDR kinases are not involved in the HCMV-mediated ligand stimulation, similar to what has been reported for murine NKG2DL during murine CMV infection (78).…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies reported that HCMV manipulates the DDR (26,27,(29)(30)(31)(32)(33)(34), a pathway able to stimulate NKG2DL and DNAM-1L expression as well (35)(36)(37)(38)(39)(40)(41)(42)(43), we examined the involvement of DDR signaling in the HCMV-mediated upregulation of activating ligands using genetic and pharmacological approaches.…”
Section: Nkg2d and Dnam-1 Ligands Contribute To The Nk Cell-mediated mentioning
confidence: 99%
See 1 more Smart Citation
“…293T human embryonic kidney (obtained from ATCC), CEM.NKr cells (obtained from David Evans, Harvard Medical School), and primary cells were grown as previously described (12,51). CD4 T lymphocytes were purified from rested PBMCs by negative selection and activated as previously described (11).…”
Section: Methodsmentioning
confidence: 99%
“…pNL43-ADA(Env)-GFP.IRES.Nef proviral vectors (deleted for vpu, nef, and nef and vpu or expressing the D368R Env variant) and the VSVG-encoding plasmid (pSVCMV-IN-VSV-G) were previously described (12,51). T/F and corresponding 6-mo consensus IMCs of patients CH58 and CH77 were inferred, constructed, and biologically characterized as described (36)(37)(38)(39).…”
Section: Methodsmentioning
confidence: 99%